Analysis of matury for project management in organizations (2020)
The purpose of this paper is to analyse the maturity of project management at the Faculty of Engineering and Architecture of the University of Pamplona. An instrument of the Kerzner-PMMM maturity model was applied. The respondents are part of the teaching and administrative academic staff. With the model chosen, a medium-low degree of maturity is observed, allowing an opportunity to unify processes and seek alternatives until a high level and success is achieved in the projects.